Customer adoption of Chat GPT for web development and programming assistance in the Zimbabwe tech industry - Alexander; Sri Widiyanesti; Indrawati, Indrawati (Adpebi Science Series, 2024)
In Zimbabwe, 60% of programmers in the IT sector express concerns about the user interface (UI) and user experience (UX) design of the web development systems they use. Additionally, 70% of the country's IT sector faces challenges that affect service quality due to software bugs and inadequate web development protocols. According to the Zimbabwe Investment and Development Agency (ZIDA), developers introduce approximately 70 bugs per 1,000 lines of code, with bug fixes taking significantly longer than initial coding efforts, leading to substantial costs for companies. This research aims to analyze the factors influencing customer adoption of ChatGPT in web development by utilizing the DeLone and McLean Success Model as a theoretical framework. Using IBM SPSS software for data analysis, 30 tech individuals who use ChatGPT for web development were surveyed. The pilot test confirmed the validity and reliability of the tool, which comprises 7 variables and 30 items, making it suitable for further research.